UNIVERSITY ENGINEERING EDUCATION AND TRAINING IN NIGERIA: DEVELOPMENT, WEAKNESSES AND IMPROVEMENTS (Nigerian Journal of Technology, 2002)
The Nigerian University engineering education and training system is be-set by a number of inadequacies - low entry standards, non-uniformity in entry process for all engineering faculties in the country, moderate academic quality of entrants for the profession, low level knowledge of Mathematics and physical Sciences for the study of the profession, short and inadequate period of academic training in the university etc. Although the system is identical with that of the British, nationally there are social industrial and economic limitations mitigating against its effectiveness in producing engineering manpower of the right calibre. Consequently, the existing system is likely to produce mostly 'calculators' instead of engineers unless it is drastically modified. A possible modification lies in the adoption of an enhanced entry requisite of a Combined Degree standard of knowledge of Mathematics and Physical science backed by well-organized industrial attachment during long vacations.